A strong early acting wound‐inducible promoter, RbPCD1pro, activates cryIAc expression within minutes of wounding to impart efficient protection against insects - Pandey, Saurabh Prakash (Plant Biotechnol J, 2019)
The expression of insecticidal proteins under constitutive promoters in transgenic plants is fraught with problems like developmental abnormalities, yield drag, expression in unwanted tissues, and seasonal changes in expression. RbPCD1pro, a rapid, early acting wound‐inducible promoter from rose that is activated within 5 min of wounding, was isolated and characterized. Wounding increased transcript levels up to 150 and 500 folds within 5 and 20 min coupled with high translation as seen by histochemical GUS enzyme activity within 5–20 min. RbPCD1pro was activated by both sucking and chewing insects and showed wound‐inducible expression in various aerial tissues of plants representing commercially important dicot and monocot families. The promoter showed no expression in any vegetative tissue except upon wounding. Functionality of RbPCD1pro was tested by its ability to drive expression of the insecticidal protein gene cryIAc in transgenic Arabidopsis and tomato. Strong wound‐inducible CryIAc expression was observed in both plants that increased 100–350 fold (Arabidopsis) and 280–600 fold (tomato) over the unwounded background within 5 min and over 1000–1600 fold within 20 min. The unwounded background level was just 3–6% of the CaMV35S promoter while wound‐induced expression was 5–27 folds higher than the best CaMV35S line in just 5 min and 80‐fold higher in 20 min. Transgenic plants showed strong resistance even to larger fourth instar larvae of H. armigera and no abnormalities in development and general plant growth. This is one of the earliest acting promoters with wide biotechnological application across monocot and dicot plants.